THE EFFECT OF USING SCRAPBOOK ON STUDENTS’ MOTIVATION AND ABILITY IN WRITING RECOUNT TEXT MA AL-QASIMIYAH SOREK SATU - Darini, Rahma (Journal of Education and Teaching, 2024)
AbstractThis research is aimed to find out whether there are significant effects of using scrapbook on the students’ motivation and ability in writing. This research designs a quasi-experimental research with non-equivalent control group design. The population of this research was 102 students of Ma Al-Qasimiyah Sorek Satu and the sample of this research is the X A for experiment class and X B for control Class. The data of this research were collected by giving the writing tests and questionnaire to the students. The results of data analysis showed: scrapbook is effective to motivated student on learning process and teaches writing, since motivation in learning English for student’s has improvement. The result of student’s writing test can be seen from the result of the t-test mean on experiment class is 2050. The probability of (Sig.) was 0.001 is smaller than 0.005 which shows a strong correlation of Scrapbook for the students’ writing ability in recount text. Then, the result of the t-test mean on control class is 6.33 and the probability of (Sig.) was 0.0023. From the result of calculation of effect size for paired sample t-test, the value of eta square is 0.59 is included in ‘Moderate Effect’ (0.51 – 1.00). It can be concluded that the implementation of scrapbook has beneficial effects. The research questions are answered that scrapbook is effective in teaching writing and giving a good effects for students’ motivation.   Key words: Scrapbook, student’ motivation, student’ writing ability